ANALYSIS OF HEALTH CONDITION BASED ON IRIS IMAGE - Ms. Pragtee Bhagvan Tathe; Mrs. Dr. M. M. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
The iris is like a map of the body .changes in certain organs is reflected in specific parts of the iris. So in health diagnosis, Iris image play very important role. So analysis of images gives the health status of organs. Medical science require easy, less time consuming diagnosis technique .Iridodiagnosis, which is the branch of medical science full fill that requirements. With the help of Iridodiagnosis different diseases can be detected. Initially the images of eye are captured, then features are extracted then classification is carried out for finding out the presence of different diseases of different organs. Present paper focus the method for detecting the diabetes.